Implementing Rhythmic Gymnastics as a Learning Strategy for Gross Motor Development in Early Childhood: A Qualitative Study - Wulan Nurlaela; Siti Ismayanti; Clevarisza Aulia Sansofa; Karista Meilinda Nuraeni; Indah Dwi Cahyawati (GENIUS: Indonesian Journal of Early Childhood Education, 2025)
Gross motor development is a crucial aspect of early childhood that requires structured and enjoyable learning strategies. This study aims to describe the implementation of rhythmic gymnastics as a strategy to support gross motor development in early childhood education. Using a descriptive qualitative approach, data were collected through observations, interviews, and documentation of rhythmic gymnastics activities conducted with children in a kindergarten setting. The findings show that rhythmic gymnastics was implemented through systematic planning, including scheduling, duration, movement variation, and the provision of a supportive learning environment, with teachers acting as facilitators and parents providing emotional support. The implementation process was associated with increased children’s engagement in movement activities and positive emotional involvement during participation. The study concludes that rhythmic gymnastics functions as a meaningful learning strategy for supporting gross motor development when implemented consistently and adaptively in accordance with children’s developmental and emotional readiness.